Variasi Struktur Morfologi Umbi dan Daun Ubi Jalar (Ipomoea batatas (L.) Lam.) Hasil Persilangan Alami Asesi Antin 1 dengan Beta 2 - ida rahmawati; Sulistiono Sulistiono; Budhi Utami (Universitas Nusantara PGRI Kediri, 2023)
The phenotype of a living thing is determined by the DNA sequence inherited from the male and female parents. The phenotype of a cross on sweet potato (Ipomoea batatas) cannot be predicted using Mendel's Law rules because the dominance/recessive trait in the parents is not known, as a result of self sterility. This study aims to describe the morphological structure of tubers and leaves resulting from natural crosses of Asesi Antin 1 and Beta 2 sweet potatoes. The study was conducted in an observational non-experimental manner on plants resulting from natural crosses of sweet potato Antin 1 with Beta 2 assesion. All seeds resulting from the crosses were germinated in soil : sand media with a ratio of 3: 1. Furthermore, the growing sprouts were planted in plastic pots with a diameter of 30 cm with a medium consisting of soil: sand: compost = 3: 2: 1,then harvested after 7 months of age. The tuber morphological structures observed were shape tuber character, skin color predominant, and tuber flesh predominant color characters, while the leaf morphological structures observed were circumscriptio, margo folii, number of lobus, and the leaf vein color. The number of seedlings that managed to grow to maturity was 10 plants and had a variety of tuber and leaf morphological structures One plant did tubers, and the other 9 plants produced of tubers.The morphological characteristics of the tubers and leaves of all individuals were as follows: 1) tuber shape characters, rounded, oblong and obovate for 1 plant each, long irregular, long oblong and ovate for 2 plants each; 2) the dominant color of tuber skin, 1 plant was purple, 5 plants were cream, and 3 plants were red; 3) the dominant color characters of tuber flesh were purple and white-purple each 3 plants, 2 plants were yellow-white and 1 plant was yellow; 4) the character of circumscriptio of triangular leaves is 3 plants and the cordatus leaves is 7 plants; 5) the character of the margo folii, 3 plants are palmati fidus, 5 plants are palmati partitus and 1 plant is palmati lobus; 6) the character of the number of lobes, 3 lobes is 3 plants, 5 lobes is 5 plants, 4 and 7 lobes is 1 plant each; and 7) the character of the vein of leave, green veins is 8 plants, purple and purple at the base only is 1 plant each.